If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 27 = 0 Reorder the terms: 27 + 13x = 0 Solving 27 + 13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 13x = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 13x = 0 + -27 13x = 0 + -27 Combine like terms: 0 + -27 = -27 13x = -27 Divide each side by '13'. x = -2.076923077 Simplifying x = -2.076923077
| 7(x-2)+1=8x-6 | | -7y-5=3-6y | | 2(x^2+4x-260)=0 | | 0.75(16-12x)-8x=-22 | | 0=(4x+1)(x-8) | | 5y-4=11y+14 | | x^2+4x-260=0 | | 8-6p-7p=31 | | 3x+3y+6=36 | | 16x-15=2x-8 | | 5z-3=z+9 | | 2=s+18 | | x^2-9x+2=36 | | 9x-5=21+3 | | 2-9t=0 | | m-39=-11 | | 7r^2-4r+7=0 | | y=-3(3)+5 | | 40a^3+5b^3= | | -3y-15=45 | | 7x+3(x-2)=6(x+1)-3 | | 2(k+5)-3=k+18 | | Y=-3(-6)+5 | | 6x^2-2=135 | | 7x-2=7(x+4) | | 5wk-3k-6k+k-10= | | 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= |